Operation of a mechanically agitated semi-continuous multi-enzymatic reactor by using the Pareto-optimal multiple front method. (May 2017) - Maria, Gheorghe; Crişan, Mara
Graphical abstract: Highlights: Optimal operation of a mechanically agitated semibatch reactor (MASCR) is determined. The multi-objective optimization problem is solved for a multi-enzymatic system case. Optimal setpoint is determined by using the generated multiple Pareto-optimal fronts. Abstract: One essential engineering problem when developing an industrial enzymatic process concerns the choice of the reactor operating alternative based on à-priori knowledge of the process kinetics and enzyme inactivation characteristics. For a multi-enzymatic system, involving complex interactions among enzymes that exhibit optimal activity on different parametric domains, and a high-order deactivation, this problem requires an extended analysis. The optimization and control engineering problems become very challenging due to the process high nonlinearity and the presence of a large number of complex constraints. All these will translate into a multi-objective optimization problem to be solved for each case. An elegant option developed in this paper is to obtain sets of Pareto optimal solutions, also called Pareto-optimal fronts, successively generated for pairs of adverse objectives. Then, the final choice of the enzymatic reactor operating policy results from the comparative analysis of these Pareto-fronts. Exemplification is made for the complex case of the oxidation of D-glucose (DG) to 2-keto-d -glucose (kDG) in the presence of P2Ox (Pyranose oxidase, EC 1.1.3.10) and catalase, continuously operated in a three-phase mechanically agitated semibatch reactor (MASCR) with co-immobilized enzymes on alginate beads. Optimal operating policy choice is based on the minimum amount of required P2Ox that ensures an imposed reaction conversion and maximum reactor productivity under various technological constraints, and for catalase/P2Ox ratios of 200–300 U/U.